Peningkatan Motorik Kasar Melalui Senam Irama bagi Anak Usia 4-5 Tahun - Roeyana, Ita (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
This study aims to determine how the use of rhythmic gymnastics to improve gross motor skills of early childhood. This research was conducted in classes B KB Desa Taruna Bangsa Tajungsari Tlogowungu Pati in the academic year 2016/2017 for two months, December 2016 to January 2017. The subjects of this research were 30 students. The method used in this research is classroom action research with two cycles. The first cycle is done in large groups and cycle II in a small groups where each group consisted of 10 people for one group. Every action done through the planning stage, acting, observing, and reflecting. The results of the research through two cycles show that an increase in the second cycle. This is shown in the power aspect there was an increase from the first cycle to the second cycle of 15 children increased to 20 children. The percentage increase of 50% from the first cycle, the second cycle to 66.67% from 15 children to 20 children experience changes that seemed to go well in executing instructions.